Pengaruh Perbandingan Fraksi Volume Serat Eceng Gondok Dan Serat Sabut Kelapa Terhadap Kekuatan Tarik Bermatrik Resin Epoxy - Endramawan, Tito; Sifa, Agus; Dionisius, Felix; Sukroni; Prasettya, S. (Journal of Applied Mechanical Technology, 2024)
The purpose of using natural fibers as reinforcement for composite materials is expected to be an alternative material to replace the used of fiberglass fibers and is expected to be able to increase the quality of water hyacinth fibers and coconut coir fibers. In this study, to determine the best tensile strength value, several experiments were carried out using the determine factor of the fiber volume fraction of 20%, 25%, 30% and the immersion factor with NaOH solution for 4 and 6 hours using a matrix in the form of epoxy resin. The test results showed that the variation of soaking in alkaline solution media (NaOH) for 6 hours with a volume fraction of 30% obtained the best tensile strength results with each type of fiber, water hyacinth fiber obtained the best results of 23.32 MPa while coco fiber the best result was 22.10 MPa.